2018
DOI: 10.5713/ajas.17.0338
|View full text |Cite
|
Sign up to set email alerts
|

miR-375 down-regulation of the rearranged L-myc fusion and hypoxia-induced gene domain protein 1A genes and effects on Sertoli cell proliferation

Abstract: ObjectiveThis study aimed to screen and identify the target genes of miR-375 in pig Sertoli (ST) cells and to elucidate the effect of miR-375 on the proliferation of ST cells.MethodsIn this study, bioinformatics software was used to predict and verify miR-375 target genes. Quantitative polymerase chain reaction (PCR) was used to detect the relationship between miR-375 and its target genes in ST cells. Enzyme-linked immunosorbent assay (ELISA) of rearranged L-myc fusion (RLF) and hypoxia-induced gene domain pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Recent studies have demonstrated that miR-221-3p functions as an oncogene in specific types of human cancer, including HCC (Wang et al, 2019), non-small cell lung cancer (Yin, Zhang & Li, 2019), glioma (Milani et al, 2019), gastric cancer and breast cancer (Deng et al, 2017). It was also reported that miR-375 inhibits the proliferation and migration of many cancer cells (Guo et al, 2018;Shen et al, 2014;Wu et al, 2017). Moreover, miR-221 promotes HCC cell migration by regulating the expression of plant homeodomain finger 2 (PHF2), which was demonstrated to be a target gene of miR-221 (Fu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that miR-221-3p functions as an oncogene in specific types of human cancer, including HCC (Wang et al, 2019), non-small cell lung cancer (Yin, Zhang & Li, 2019), glioma (Milani et al, 2019), gastric cancer and breast cancer (Deng et al, 2017). It was also reported that miR-375 inhibits the proliferation and migration of many cancer cells (Guo et al, 2018;Shen et al, 2014;Wu et al, 2017). Moreover, miR-221 promotes HCC cell migration by regulating the expression of plant homeodomain finger 2 (PHF2), which was demonstrated to be a target gene of miR-221 (Fu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more and more studies have confirmed that miRNA is involved in a variety of diseases and pathophysiological processes of tumors. Studies have reported that miR-375 plays an important role in myocardial infarction repair and testicular cell proliferation [2,3], but its role in bronchial epithelial cells is not yet clear. Kr€ uppel-like transcription factors (KLFs) form a subclass of $17 zinc fingers, which contain a DNA-binding transcription factor expressed in humans and belong to the specific protein 1 (Sp1)/KLF zinc finger-binding transcription factor family [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The next identified biomarker gene is COLCA2 (ENSG00000214290), which participates in the tumorigenesis of colorectal cancer ( Loo et al, 2017 ; Guo et al, 2018 ). As for the relationship between the expression of such gene and viral infection in the respiratory system, COLCA2 has been correlated with the dysfunction of lung tissues under chronic diseases, including chronic obstructive pulmonary diseases ( Verma, 2016 ) and chronic viral infection ( Shi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%